Time-energy optimal control of vector controlled induction motor - Alli, H; Bayindir, MI (Emerald Group Publishing Ltd, 2002)
A time-energy optimal position control algorithm based on the Pontryagin's maximum principle is developed for a vector-controlled induction motor system. The vector-controlled induction motor is modeled as a second-order system. Bang-off-bang control profile, which operates on the torque current, is found as a minimum time-energy filter, U,here the amplitude of the time-delayed signals are constrained to satisfy Me control bounds. The time-energy objective function subject to the constraints, which satisfy boundary conditions, is solved as a parameter optimization problem by using MATLAB optimization-toolbox. To corroborate the validity of the results of the parameter optimization problem, an experimental test is performed with a dSPACE control card and 2.2 kW induction motor. Furthermore, the simulation results are verified by the switching function obtained from solving the initial conditions. Finally, Me theoretical and experimental results are graphically presented and it is seen that the results are in very close agreement.
Keywords: control; induction motor